Scenography of three picture books and scenography of their reading in class-some references that turn out to be problematic - Tauveron, Catherine (Ondina - Ondine, 2020)
Our corpus is composed of a training program aiming for literary reading through picture books and course preparations by future primary school teachers. Two major references have been selected, which guide the choice and the analysis of the picture books as well as the students’ preparations: it is the categorization of S. Van der Linden, which distinguishes redundancy, collaboration and disjunction links between texts and images, and the opposition posed by Isabelle Nières-Chevrel between theverbal narrator and the visual narrator. We show how these two references prove to be impertinent toanalyze and make effective reading in class of three picture books (Mon chat le plus bête du monde, Balthazar! and L’Afrique de Zigomar) gathered because they seem to have a common denominator (“contradiction between narrator in words and narrator in pictures”). If there is a gap between text and images in these three picture books, the text / images links are in each of different nature and status, theproblems of comprehension, which will arise for the pupils, are in each case singular and not related tothe supposed double narrative. We propose an alternative analysis of these picture books and a singulardidactic scenography to solve the comprehension problems detected.Key words: picture books (Mon chat le plus bête du monde, Balthazar !, L’Afrique de Zigomar),text/images relations, relation to the truth, problems of comprehension, didactic scenography.